Kinship analyses in forensic genetics: when complex hypotheses meet (very) complex genotypes - Marisa Faustino; Leonor Gusmão; António Amorim; Daniel Kling; Nádia Pinto (RevSALUS, 2025)
Kinship analyses unlock the power of genetic data to unravel biological relationships and identify individuals. While most cases involve paternity/maternity problems using autosomal markers, more challenges arise when more complex kinship cases are investigated or when the information given by autosomal markers alone provide inconclusive results. In such cases, it might be useful to analyze the X chromosome due to its unique features, specifically its haplodiploid mode of transmission and recombination pattern, which have been proven to be powerful to complement the information given by the autosomes or to solve complex kinship cases [1]. Theoretical and statistical frameworks were already established assuming euploid individuals, failing to address those with an X chromosome aneuploidy [1], such as those with Trisomy X (47, XXX), Klinefelter (47, XXY) and Turner (45, X0), which are the most common. Many individuals remain undiagnosed due to the absence or presence of mild symptoms, leading to an underestimated population prevalence [2]. To address this gap, we developed an innovative biomathematical framework able to handle the X chromosome aneuploidies mentioned, accommodating all the kinship hypotheses linking a pair of non-inbred individuals (euploid/aneuploid). Our research was trigged by a real case [3] and revealed an impressive increase in the complexity compared with the analysis of exclusively euploid individuals. We established the algebraic formulae for the framework and observed that they depend not only on the kinship hypotheses at stake but also on the genotypic configurations of the individuals, and origin of the parental error (maternal or paternal). Additionally, we investigated the probability of the individual with an aneuploidy inheriting a pair of identical-by-descent (IBD) alleles from the disomic gamete. For some cases, this probability can be inferred given the genotypes and the kinship hypothesis considered, while for the remaining cases, we recommend using an estimation of this value (0.37 for pericentromeric markers and 0.33 for centromeric ones). Notably, while it is possible for non-inbred individuals with an aneuploidy to present two alleles that are IBD in their genotype, this doesn’t occur for non-inbred euploid individuals. This highlights the added complexity and distinct inheritance patterns introduced by X chromosome aneuploidies. This research will enhance the kinship analyses when one of the individuals is euploid and the other presents an X chromosome aneuploidy, offering new insights into the interpretation of DNA profiles and its evaluation in the different contexts where they can be useful in the scientific setting.